Steady-state Auditory Evoked Potentials: Review - Barajas del Prat, José Juan; Zenker, Franz (Auditio, 2021)
The early diagnosis of hearing loss should be carried out early in view of the implications that the lack of auditory stimulation has on the development of language and speech. Up to six months, behavioral audiometries are not reliable, so at these ages, newborns are evaluated using Otoacoustic Emissions (OAE) and Auditory Brainstem Responses (ABR). However, these techniques are not capable of deriving selective information from the cochlear partition. Auditory Steady-state Responses (ASSR) are a periodic evoked brain response in time whose frequency remains constant in amplitude and phase. For audiometric purposes ASSRs have several advantages over ABRs. First, through statistical procedures, the presence of response is determined, increasing the reliability and validity of the technique. Second, ASSR allow the use of frequency-specific tones. Third, ASSR allow the derivation of specific information on the frequency of the cochlear partition. This article reviews the principles and foundations of this electrophysiological technique.